Functional outcomes after the Ross (pulmonary autograft) procedure assessed with magnetic resonance imaging and cardiopulmonary exercise testing. Issue 4 (18th June 2009) - Puranik, Rajesh; Tsang, Victor T; Broadley, Andrew; Nordmeyer, Johannes; Lurz, Phillip; Muthialu, Nagarajan; Derrick, Graham; Walker, Fiona; Cullen, Seamus; de Leval, Marc; Bonhoeffer, Phillip; Taylor, Andrew M; et al.
Abstract : Objective: To assess autograft, homograft and ventricular function, as well as exercise capacity, in adult patients who have undergone the Ross procedure. Setting: Single centre paediatric and adult congenital heart disease unit. Patients: 45 subjects (24.6 years, range 16.9–52.2 years) who underwent the Ross procedure between 1994 and 2006 (8.1 years after the Ross operation, range 2.0–14.0 years). Interventions: Cardiovascular magnetic resonance imaging, echocardiography and cardiopulmonary exercise testing. Main outcome measures: Autograft and homograft stenosis, and regurgitation. Autograft size. Biventricular function, scar volume and exercise capacity. Results: Mean autograft regurgitation was 6.8%±8.3% (trivial regurgitation) and diameter was 40.0±7.0 mm. Mean homograft velocity was 2.4±0.6 m/s (mild-moderate stenosis) and regurgitation was 6.1%±8.3% (trivial regurgitation). Biventricular systolic function was normal (LV EF 63.1±6.4% and RV EF 60.1%±7.6%). In 38% of cases there was evidence of LV scar, mostly noted within the inter-ventricular septum. The mean exercise capacity achieved was 87%±22% of predicted. There was no correlation between exercise capacity and ventricular function or scar. Conclusion: This study demonstrates minor autograft and homograft dysfunction in the majority of patients after the Ross procedure, associated with good ventricular function and exercise capacity. In addition, minor scar was present in a third of patients with no functional consequences.